Adipose-Derived Stromal Cells Attenuate Adipose Inflammation in Obesity through Adipocyte Browning and Polarization of M2 Macrophages - Zhang, Wen-Chao; Qin, Feng; Wang, Xiao-Jun; Liu, Zhi-Fei; Zhu, Lin; Zeng, Ang; Zhang, Ming-Zi; Yu, Nan-Ze; Long, Xiao (Mediators of Inflammation, 2019)
Obesity is a metabolic condition associated with multiple health problems such as endocrine and metabolic dysfunction and chronic inflammation in adipose tissues. In this study, the ADSCs could be stimulated to differentiate into brown adipocyte with rosiglitazone treatment based on the Oil-Red-O staining trial. Furthermore, the multilocular lipid droplets located in the center was increased in differentiated brown adipocytes, and brown fat-associated proteins, UCP1, PPAR-γ, and LPL were highly expressed in brown adipocytes differentiated from ADSCs. Additionally, the results of animal experiments showed that both weight and amount of VLDL and LDL were decreased in the serum of obese mice after transplantation of rosiglitazone-induced brown adipocytes, while the level of HDL increased. Moreover, the proteins associated with lipid metabolism, LPA and UCP1, were downregulated, and the inflammatory response was suppressed through inhibition of the ITGAM/NF-κB-mediated proinflammatory responses and polarization of M2 macrophages. Similarly, the amounts of proinflammatory cytokines, TNF-α, IL-6, and IL-1β were decreased after rosiglitazone-induced brown adipocyte transplantation. On the contrary, anti-inflammatory cytokine IL-10 was significantly increased in both groups of obese mice, with or without brown adipocyte transplantation. Therefore, the adipose-derived stromal cells with induced browning could promote lipid consumption and alternative polarization of M2 macrophages to attenuate adipose inflammation in obesity mouse models, which thus provides a potential therapy for obesity.